Bland–Altman Analysis of Different Radiographic Measurements of the Hallux Valgus Angle and the Intermetatarsal Angle After Distal Osteotomy. Issue 6 (27th August 2020) - Cao, Xuhan; Bai, Zixing; Sun, Chengyi; Wen, Jianmin; Lin, Xinxiao; Sun, Weidong
Abstract : Objective: The aim of the present study was to evaluate commonly used approaches for detection of radiographic angles in hallux valgus deformity patients. Methods: This retrospective study was conducted in patients with hallux valgus deformity at Wangjing Hospital of China Academy of Chinese Medical Sciences from January 2016 to January 2019. The inclusion criteria were: (i) postoperative dorsoplantar weight‐bearing radiographs for the feet of patients with the hallux valgus; (ii) patients had been managed with a distal osteotomy of the first metatarsal and the osteotomized bone ends recovered. The exclusion criteria applied were as follows: (i) age > 65 years or < 18 years old; (ii) blurry image; (iii) previous history of severe foot trauma and surgery. Postoperative radiographs for hallux valgus were analyzed using six methods: by a line drawn through the long axis of the first metatarsal bone (method 1); an extended line drawn to bisect the shaft of the metatarsal at two levels with joined points of bisection (method 2); a line drawn to connect the center of the articular surface of the metatarsal head and the center of the proximal articulation (method 3); a line drawn from the center of the head of the first metatarsal head through the center of the base of the first metatarsal bone (method 4); a line drawn through the center of the head and the center of the proximal shaft (method 5); and a line drawn from the center of the head of the first metatarsal head through the center of the proximal articulation (method 6). The measurement results obtained were subjected to Bland–Altman analysis and consistency evaluation. Results: A total number of 20 radiographs were collected for measurement. No statistically significant differences were found in the measurement values among the six methods ( P > 0.05). The lowest values of the average measurement, standard deviation, and confidence interval were established in method 3, followed by those in methods 1 and 4. The standard deviation of the measurement value and the confidence interval in method 2 were the largest. Methods 1 and 4 had similar confidence intervals and were with a high consistency. Due to the nature of the retrospective study, no follow‐up and complications were applicable in the present study. Conclusion: Line drawn through the long axis of the first metatarsal bone (method 1) and line drawn from the center of the head of the first metatarsal head through the center of the base of the first metatarsal bone (method 4) were reliable and well repeatable, and may be used for postoperative radiographs.